2010
DOI: 10.1038/emboj.2010.197
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor PPARγ individually responds to serotonin- and fatty acid-metabolites

Abstract: The nuclear receptor, peroxisome proliferator-activated receptor c (PPARc), recognizes various synthetic and endogenous ligands by the ligand-binding domain. Fattyacid metabolites reportedly activate PPARc through conformational changes of the X loop. Here, we report that serotonin metabolites act as endogenous agonists for PPARc to regulate macrophage function and adipogenesis by directly binding to helix H12. A cyclooxygenase inhibitor, indomethacin, is a mimetic agonist of these metabolites. Crystallographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
125
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 74 publications
7
125
0
3
Order By: Relevance
“…Recent study showed that some combinations of ligands, fatty acid and indole acetate or indomethacin, induce additive orsynergistic activation of PPARg. 27 This study confirmed the data about the combination effect of telmisartan and glimepiride. We do not have definitive data about the binding site of glimepiride to PPARg.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Recent study showed that some combinations of ligands, fatty acid and indole acetate or indomethacin, induce additive orsynergistic activation of PPARg. 27 This study confirmed the data about the combination effect of telmisartan and glimepiride. We do not have definitive data about the binding site of glimepiride to PPARg.…”
Section: Discussionsupporting
confidence: 81%
“…Telmisartan binds to helixes H3 and H7 of LBD of PPARg does TZD and other partial agonists of PPARg. 7,26,27 Difference of binding ability (to H12) might bring different degrees of activation of PPARg. The carboxy terminal activation domain (AF-2) in H12 of LBD is proposed to undergo induced conformational changes after binding to ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor g (PPARg) is a member of the lipid-activated nuclear receptor family and has been implicated in differentiation, inflammation, and lipid metabolism in cells of the innate immune system, including macrophages (11)(12)(13)(14). Testicular receptor 4 (TR4) is another nuclear receptor, along with PPARg, that may function as a fatty acid sensor (12,(14)(15)(16); it is highly expressed but without a defined role in macrophages. Analysis of gene expression of the nuclear receptor superfamily after activation highlighted the presence of 28 nuclear receptors in murine macrophages.…”
mentioning
confidence: 99%
“…42 The ligand binding site of LBD of PPARγ has two sub-pockets on the center of Helix 3 (H3) (Figure 4(a)); One pocket is included H12 and another is located on H5 region. Whereas the full agonists occupy these two pockets, the partial agonists bind to only one pocket on H5.…”
Section: -41mentioning
confidence: 99%
“…Whereas the full agonists occupy these two pockets, the partial agonists bind to only one pocket on H5. 42 In the case of a full agonist indomethacin, two indomethacin molecules bind to LBD. Two carboxyl groups of indole acetate moiety in indomethacin form hydrogen bonding interactions with His 323 on the H4 and Tyr473 on the H12 of hPPARγ.…”
Section: -41mentioning
confidence: 99%